Strategi Menciptakan Swasembada Pangan Melalui Program Desa Mandiri Pangan (DEMAPAN) di Dinas Pertanian dan Ketahanan Pangan Kabupaten Tangerang - Trisya Walza Rizkita; Irvan Arif Kurniawan; Hilman Hilman (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2025)
The Indonesian government prioritizes food self-sufficiency to ensure food availability and affordability as a pillar of national stability. The Food Self Sufficient Village Program (DEMAPAN) was launched as an effort to achieve food self-sufficiency at the village level, with Sodong Village as the pilot project location in 2024. This study aims to analyze the strategies employed by the Agriculture and Food Security Department of Tangerang Regency in creating food self-sufficiency through the Food-Self-Reliant Village Program (DEMAPAN) in Sodong Village, as well as the challenges faced. The research method used is descriptive qualitative, involving observation, interviews, and documentation. This study employs Kooten's theory as cited in Salusu (2006). Program Strategy, and Institutional Strategy have been implemented optimally through synergy between the Department, Village Government, and community groups, successfully increasing farmers' income, access to nutritious food, and sustainable training. However, in the dimension of Resource Support Strategy, the results have not been optimal due to constraints such as labor shortages, declining member motivation, and issues related to fund and land management. Other challenges include limited budgets, expensive agricultural equipment, and unfavorable land conditions. To achieve optimal results, it is necessary to enhance resource support, provide continuous training, and pay special attention to motivation management and human resource development.